Cơ học kết cấu - Lều, Thọ Trình (Khoa học và kỹ thuật, 2006)
KR407 Cơ học công trình 02; XD026 Cơ học kết cấu 1 - Tĩnh định ; XD027 Bài tập lớn Cơ học kết cấu 1 - Tĩnh định; XD302 Cơ học kết cấu 1 - Tĩnh định